Assessment of access to health products, technologies and services among the BRICS through their health indicators and their participation in global health policy - Soares , Rosa Leonôra Salerno (Seven Editora, 2023)
In the OMS Constitution, the preamble states that the health of all peoples is fundamental to the attainment of peace and security, and that the achievement of any state in promoting and protecting health is of value to all. Thus, the global health issue is part of all discussions of global diplomacy in the 21st century. Since 2001, identified as the main countries in their regions, Brazil, Russia, India and China have grown in economic terms in addition to adopting activist foreign policies. Identified as a geopolitical bloc since 2006, the BRICS believe they have the right to play more relevant roles in the management of the global order in the 21st century. Despite exhibiting many regional differences, the member countries of the BRICS strive to be recognized as members of the same group through some strategies such as participation in international institutions and the effort to create connections between development and foreign policy. Many analysts suggest that the BRICS are more active in global health. Recently, this group of countries increased their cooperation in the field of social development, environmental protection and health, institutionalized regular meetings of their ministers of health, with stated objectives to address emerging health threats, both for their populations and globally. Thus, we consider that the presentation of a comparative panel of health indicators of the countries that make up the BRICS is useful for researchers in the area. DOI:https://doi.org/10.56238/globalhealthprespesc-067